Quality assessment of evidence-based clinical practice guidelines for the management of pregnant women with sickle cell disease using the AGREE II instrument: a systematic review - Yasser S. Amer; Yasser Sabr; Ghada M. ElGohary; Amer M. Altaki; Osamah T. Khojah; Ahmed El-Malky; Musa F. Alzahrani (BMC, 2020)
Abstract Background The management of pregnant women with sickle cell disease (SCD) poses a major challenge for maternal healthcare services owing to the potential for complications associated with morbidity and mortality. Trustworthy evidence-based clinical practice guidelines (CPGs) have a major impact on the positive outcomes of appropriate healthcare. The objective of this study was to critically appraise the quality of recent CPGs for SCD in pregnant women. Methods Clinical questions were identified and the relevant CPG and bibliographic databases were searched and screened for eligible CPGs. Each CPG was appraised by four independent appraisers using the AGREE II Instrument. Inter-rater analysis was conducted. Results Four eligible CPGs were appraised: American College of Obstetricians and Gynecologists (ACOG), National Heart, Lung, and Blood Institute (NHLBI), National Institute of Health and Care Excellence (NICE), and Royal College of Obstetricians and Gynaecologists (RCOG). Among them, the overall assessments of three CPGs (NICE, RCOG, NHLBI) scored greater than 70%; these findings were consistent with the high scores in the six domains of AGREE II, including:[1] scope and purpose,[2] stakeholder involvement,[3] rigor of development,[4] clarity of presentation,[5] applicability, and [6] editorial independence domains. Domain [3] scored (90%, 73%, 71%), domain [5] (90%, 46%, 47%), and domain [6] (71%, 77%, 52%) for NICE, RCOG, and NHLBI, respectively. Overall, the clinical recommendations were not significantly different between the included CPGs. Conclusions Three evidence-based CPGs presented superior methodological quality. NICE demonstrated the highest quality followed by RCOG and NHLBI and all three CPGs were recommended for use in practice.